National culture as a moderator between social norms, religiosity, and tax evasion: Meta-analysis study - T. Sutrisno; Muh Dularif (Cogent Business & Management, 2020)
The objective of this research is to present the meta-analysis results of the relationship of social norms and religiosity with tax evasion, with national culture as a moderating variable. Previous researches show mixed results of the relationship between social norms, religiosity, and tax evasion. Meta-analysis is considered a way out of saturated and inconsistent research since it provides an efficient and systematic approach to make a robust conclusion. This research synthesizes 54 results of 14 individual articles published from 1989 to 2017. This study shows three main findings. Although social norms are not effective to fight tax evasion, religiosity is a useful instrument to decrease tax evasion. Theoretically, national culture plays a pivotal role as a variable to moderate social norms with tax evasion. However, this variable can not moderate religiosity with tax evasion. These findings show that the Theory of Planned Behavior inconsistently predicts the influence of social norms on tax evasion. Practically, tax authorities should consider involving religious leaders to encourage the awareness of tax compliance and to decrease tax evasion.
Keywords: H23; K42; 650; Hofstede’ s cultural dimension; meta-analysis; religiosity; social norms; tax evasion